Diet and physical activity in people with intermediate cardiovascular risk and their relationship with the health-related quality of life: results from the MARK study. Issue 1 (December 2016) - Sanchez-Aguadero, Natalia; Alonso-Dominguez, Rosario; Garcia-Ortiz, Luis; Agudo-Conde, Cristina; Rodriguez-Martin, Carmela; de Cabo-Laso, Angela; Sanchez-Salgado, Benigna; Ramos, Rafel; Maderuelo-Fernandez, Jose; Gomez-Marcos, Manuel; Recio-Rodriguez, Jose
Abstract Background To analyze the interplay between diet, physical activity and health-related quality of life in a Spanish randomly selected sample of individuals attended in general practitioners offices with intermediate cardiovascular risk. Methods This study analyzed 314 subjects, aged 35–74 years (50.6% women), from the MARK study, conducted in Spain. Health related quality of life was measured by the SF-12 questionnaire. The assessment of the lifestyles included the diet quality index, the adherence to the Mediterranean diet and the leisure time physical activity practice. Results The highest values of health related quality of life were obtained in the area of vitality (51.05 ± 11.13), while the lowest were found in the general health (39.89 ± 8.85). In the multiple linear regression analysis, after adjustment for age, gender and other confounders, for each point of increase in the Mediterranean diet adherence score, there was an increase of 1.177 points in the mental component value (p  < 0.01). Similarly, for each point of increase in the Diet Quality Index Score, there was an increase in the mental component of 0.553 (p  < 0.05). Likewise, the physical activity was positively associated with the physical function and vitality (β = 0.090 and 0.087, (p  < 0.01 andp  < 0.05), respectively). Conclusions In people with intermediate cardiovascular risk, better food habits and greater adherence to the Mediterranean diet are associated with higher scores on the mental component of quality of life. Likewise, increased physical activity is related with positive scores on the physical function.